ACCOUNTING INFORMATION TECHNOLOGY IN TAX ADMINISTRATION: CORETAX SYSTEM TRAINING FOR CHURCH CONGREGATION MEMBERS IN SURABAYA - Renna Magdalena; Josephine Kurniawati Tjahjono; Go George Herbert; Imelda Alodia Arditya; Florencia Chyntike Setiawan (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The implementation of the Coretax System beginning in 2025 marks a fundamental shift in Indonesia's tax administration infrastructure, introducing a fully integrated accounting information technology platform that affects all taxpayer categories. Despite its potential to improve efficiency and transparency, many taxpayers within community settings lack the technical readiness to operate the system correctly. This paper reports on a Community Service (Pengabdian Kepada Masyarakat/PKM) activity conducted by the Tax Center, Accounting Study Program, Universitas Pelita Harapan Surabaya Campus, held on March 6, 2026 at GSJA Ebenhaezer Church, Surabaya. The workshop was specifically designed for members of the church congregation, comprising professionals, employees, and small business owners who share the common need to fulfill their annual tax obligations through the new Coretax platform. Through a hands-on training format covering Coretax account activation and the practical filing of the 2025 Annual Tax Return (SPT Tahunan), the workshop successfully met its target attendance of at least 25 participants, with over 85% completing the full session. Findings indicate that structured, community-embedded accounting information technology training significantly improves participants' confidence and competence in using the Coretax System. This initiative demonstrates that university Tax Centers can serve as effective bridges between government-led digital tax reform and the practical readiness of community-based taxpayer groups.